Optimal renewable generation mix of hydro, wind and photovoltaic for integration into the Portuguese power system - Sousa, Jorge A. M. (2020)
In spite of the advantages of renewable energy sources (RES), their variability and uncertainty raises important issues in power systems operation, such as the need to balance demand with a highly variable and uncertain power generation. In this context, is of utmost importance the choice of the optimal renewable generation mix to be integrated in the power system in order to accomplish the established renewable energy targets with the lowest technical impacts. With this aim, this paper presents a methodology that supports decision making on the renewable energy policy by deriving the optimal renewable generation mix from different available technologies - hydro, wind and photovoltaic - that integrates a given amount of electricity from renewable sources, taking into account the variability of the renewable generation mix and the target share of renewable generation. This methodology is applied to a case study of one month using renewable generation data of the Portuguese power system.